Indications of Anti-Inflammatory Drugs in Cardiac Diseases - Algalarrondo, Vincent; Boycott, Hannah; Eliahou, Ludivine; Mabille, Mylene; S. Slama, Michel (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2013)
Throughout the history of cardiology, physicians have attempted to treat cardiac inflammatory diseases in a multitude of different ways. In recent years, three major developments have confirmed the important role of antiinflammatory drugs in cardiology: the development of new, more powerful drugs, the advent of evidence-based medicine, and the decline of rheumatic disease in western countries. Thus, we aim to review the indications for anti-inflammatory drugs in pericarditis and myocarditis. The management of pericarditis has been improved following the publication of the European guidelines in 2004. Indeed, recent randomized controlled trials highlighted the role of colchicine to i) prevent and treat recurrences of acute pericarditis and ii) prevent post pericardiectomy syndrome and its complications. With regard to the management of myocarditis, significant advances have been made towards further understanding the mechanisms involved, and in the identification of its underlying causes (especially viral vs. autoimmune). In addition, cardiac MRI and endomyocardial biopsy are now used to detect rare etiologies of myocarditis, which may benefit from immunosuppressive therapy (giant cell and eosinophilic myocarditis, cardiac sarcoidosis). Although broad consensus has yet to be reached regarding the management of acute myocarditis, identifying viral vs. autoimmune myocarditis allows a tailored treatment using antiviral or immunosuppressive drugs.
Keywords: colchicine